Double octave L‐ and S‐band power amplifier utilizing broadside coupled impedance transformers. Issue 3 (17th December 2015) - Preis, Sebastian
ABSTRACT: In this article, the recently revived impedance transformer, implemented as broad side coupled microstrip structure, is used to realize a double octave wideband power amplifier covering the L‐ and S‐band. Several parameters of the transformer, such as distance to a ground plane or permittivity of the dielectric surrounding the transformer are analyzed. The manufactured amplifier, using a commercial GaN HEMT transistor, achieved a continuous wave output power of 45 to 47 dBm and drain efficiency of 42 to 49 percent, respectively. To prove the usability of the concept, linearity measurements were performed, using LTE, WiMAX, and WCDMA signals with up to 10 MHz bandwidth at several center frequencies. ACLR results of −45 dBc are achieved using linearization, as well as an average PAE of up to 29 percent. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:209–216, 2016.